2015
DOI: 10.1002/uog.14811
|View full text |Cite
|
Sign up to set email alerts
|

Serum placental growth factor in the three trimesters of pregnancy: effects of maternal characteristics and medical history

Abstract: Objective To define the contribution of maternal variables which influence the measured level of maternal serum placental growth factor (PlGF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
148
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 24 publications
16
148
1
1
Order By: Relevance
“…A limitation of this study is the relatively small number of cases, but we find these numbers to be comparable to previous casecontrol studies investigating serum cytokines in hypertensive pregnancy disorders, 33,34,53 and our study includes a larger control group. Because our medium-to high-risk cohort predominantly included women developing late-onset gestational hypertension or preeclampsia, the findings presented here should be followed-up in a general pregnant population with larger groups, including early-and late-onset disease.…”
Section: Downloaded Fromsupporting
confidence: 64%
“…A limitation of this study is the relatively small number of cases, but we find these numbers to be comparable to previous casecontrol studies investigating serum cytokines in hypertensive pregnancy disorders, 33,34,53 and our study includes a larger control group. Because our medium-to high-risk cohort predominantly included women developing late-onset gestational hypertension or preeclampsia, the findings presented here should be followed-up in a general pregnant population with larger groups, including early-and late-onset disease.…”
Section: Downloaded Fromsupporting
confidence: 64%
“…They also found increased serum PlGF in PGDM, at least in the non-insulin-dependent subgroup. Newer data however found that serum PlGF was decreased in women with diabetes mellitus type 1 and in those with type 2 disease requiring treatment with insulin [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and inflammation alter angiogenic and anti-angiogenic factors in the placenta [10], and maternal serum levels of PlGF are reduced in the first trimester of pregnancies that will develop preeclampsia (PE) or small for gestational age infants [11,12]. While earlier studies reported increased PlGF levels in pre-gestational diabetes (PGDM) and GDM [13], a recent publication demonstrated that in PGDM first-trimester maternal serum levels of PlGF are reduced [14], while yet another study showed again increased PlGF levels in pregnancies that developed GDM [15]. …”
Section: Introductionmentioning
confidence: 99%
“…PIGF levels also decrease in the second and third trimesters of pregnancy when PE is advanced or in women having SGA neonates. Thus, a relationship may exist between PE and SGA neonates [15].…”
Section: Pro-angiogenic Markersmentioning
confidence: 99%